The Demand Curves from a Quadratic Utility Indicator - Wegge, L. L. (Review of Economic Studies, 1968)
Journal Article The Demand Curves from a Quadratic Utility Indicator Get access L. L. Wegge L. L. Wegge University of California, Davis Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 2, April 1968, Pages 209–224, https://doi.org/10.2307/2296549 Published: 01 April 1968